EDUCATOR TERMS BASED ON HADITH REVIEW - Junaidi Arsyad (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to track and find out what terms are often used for the term educator, which in this case examines the term or equivalent of the word educator in the traditions of the Prophet. The method used in this study uses a qualitative research method with an analytical descriptive approach. Where this research approach seeks to explain a symptom, event or event that is happening at the present time when the researcher tries to photograph the events and events that are the center of attention and then describe what they are related to the term educator in the hadith review. The results show that there are at least six terms or vocabulary in using the term educator in the Prophet's hadith, namely Ustadz, Mua'allim, Murabbi, Mursyid, Mudarris, Mu'addib. Where each of these vocabularies has different meanings and characteristics related to an educator.